1991
DOI: 10.1139/v91-151
|View full text |Cite
|
Sign up to set email alerts
|

Densities and viscosities of binary and ternary liquid mixtures at 25 °C

Abstract: TEJRAJ M. AMINABHAVI, SHRIKANT S. JOSHI, RAMACHANDRA H. BALUNDGI, and SHYAM S. SHUKLA. Can. J. Chem. 69, 1028 (1991).Densities and viscosities of ten binary and four ternary mixtures containing bromoform, bromobenzene, chlorobenzene, toluene, mesitylene, and dimethylformamide at 25°C have been measured over the whole range of mixture compositions. Excess molar volumes, apparent values of excess molar viscosities, and Gibbs energy of activation of flow have been calculated for these mixtures. The calculated res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This may be qualitatively interpreted in terms of closer approach of unlike molecules leading to reductions in compressibility and volume [40,42]. This type of interactions for the binary mixture DMF-toluene [47], DMF-water [48] has been already reported. The pronounced compressibility minimum at x = 0.2 may be attributed to strong molecular interaction which eventually results in complexation [48].…”
Section: Resultssupporting
confidence: 55%
“…This may be qualitatively interpreted in terms of closer approach of unlike molecules leading to reductions in compressibility and volume [40,42]. This type of interactions for the binary mixture DMF-toluene [47], DMF-water [48] has been already reported. The pronounced compressibility minimum at x = 0.2 may be attributed to strong molecular interaction which eventually results in complexation [48].…”
Section: Resultssupporting
confidence: 55%
“…Negative values of Δ throughout the whole composition range and at all temperatures suggest that the intermolecular interaction becomes weaker on mixing of components, also indicating that the dispersion type [17] of forces is predominant in these mixtures. The negative Δ values support the positive values and account for dispersive forces in these binaries.…”
Section: Resultsmentioning
confidence: 97%
“…A series of systematic investigations have been carried out on the excess molar volume ðV E m Þ of different binary mixtures of DMF with single aromatic hydrocarbon by different scientists using different methods [1][2][3][4][5][6][7][8][9][10] at the range of temperature 298.15 K to 313.15 K. Results of these experiments are quite different from each other. Some authors only reported V E m , did not report the density q.…”
Section: Introductionmentioning
confidence: 99%